(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Disaster refers to death, loss of human life, economic disruption & deterioration of health and health related services Disasters are not confined to a particular part of the world. They can occur at any place at any time. Major disasters or emergencies occurred throughout the history and as the world population grows and the resources become more limited, communities are increasingly becoming more vulnerable to the hazards that cause disaster. The statistics gathered since 1969 shows a rise in the number of people affected by disasters. The number of injuries and deaths differs depending on the number of factors such as the type of disaster, the density and distribution of the population, condition of the environment, and degree of the preparedness and opportunity of the warning. We can minimize the death, ecological disruption and deterioration of the health services by proper planning and management. JCMCTA 2014 ; 25 (2) : 3-6